Rent-Seeking Theory in the Asymmetry of Blue Economy Benefit Distribution: Economic and Sustainability Accounting Perspectives - Fety Widianti Aptasari (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2025)
The blue economy offers great potential for growth, but the unequal distribution of benefits creates serious inequalities. This research explores the impact of unequal access to marine resources, particularly for small-scale fishers and indigenous communities, through the lens of rent-seeking theory and sustainability accounting. The privatization of coastal resources often enriches large corporations while marginalizing local communities, undermining food security and leading to human rights violations. In addition, renewable energy projects in coastal areas reflect a disregard for social and ecological values that exacerbate resource conflicts. The analysis shows that top-down governance widens the gap, while traditional reporting fails to capture the social and environmental externalities of resource exploitation. The study highlights the importance of Social Return on Investment (SROI)-based reporting approaches and environmental cost-based accounting to measure the holistic impact of blue economy policies. The marginalization of women in the fisheries sector, which is often not recognized in formal reporting, underscores the need for gender-based accounting. As a solution, genuine, not just symbolic, participation of local communities must be integrated in inclusive governance. Reporting approaches such as Integrated Reporting and the Global Reporting Initiative (GRI) can map economic, social and ecological dimensions in a more balanced way. With strengthened accountability and a comprehensive sustainability framework, the blue economy has the potential to be a tool for equitable growth, protecting the rights of local communities while keeping ecosystems in balance